2004
DOI: 10.1111/j.1365-2672.2004.02248.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic properties, drug susceptibility and genetic relatedness of Stenotrophomonas maltophilia clinical strains from seven hospitals in Rio de Janeiro, Brazil

Abstract: Aims: To investigate phenotypic aspects including biotyping, drug susceptibility and production of extracellular enzymes and genetic diversity of Stenotrophomonas maltophilia clinical strains obtained from seven hospitals in Rio de Janeiro, Brazil. Methods and Results: Thirty-nine S. maltophilia strains were investigated by biotying, susceptibility testing, extracellular enzymes detection and by randomly amplified polymorphic DNA (RAPD)-PCR. Biotyping distinguished 13 biotypes among 39, and one of them was pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 34 publications
(44 reference statements)
4
17
0
Order By: Relevance
“…While soil and plants are its main environmental reservoir (RYAN et al, 2009), this bacterium has also been isolated from diverse effluent treatment plants and wastewater (YU; LIU; WANG, 2009;VERMA et al, 2010) and from a Brazilian sugar cane variety (RAMOS et al, 2011). In agreement with the results obtained, some researchers have described the production of extracellular enzymes by Stenotrophomonas including proteases, lipases, nucleases, and chitinases (TRAVASSOS et al, 2004;KUDDUS, RAMTEKE, 2011). Stenotrophomonas sp.…”
Section: Discussionsupporting
confidence: 75%
“…While soil and plants are its main environmental reservoir (RYAN et al, 2009), this bacterium has also been isolated from diverse effluent treatment plants and wastewater (YU; LIU; WANG, 2009;VERMA et al, 2010) and from a Brazilian sugar cane variety (RAMOS et al, 2011). In agreement with the results obtained, some researchers have described the production of extracellular enzymes by Stenotrophomonas including proteases, lipases, nucleases, and chitinases (TRAVASSOS et al, 2004;KUDDUS, RAMTEKE, 2011). Stenotrophomonas sp.…”
Section: Discussionsupporting
confidence: 75%
“…Given the conservation of xps genes among four other S. maltophilia genomes, we infer that Xps T2S is active in other strains of S. maltophilia. In support of this hypothesis, we along with other investigators have found protease activities in supernatants from a variety of other strains of S. maltophilia (3,20,23,45,46). The ϳ47-kDa protein that we observed in the K279a supernatant but not in the xps mutants' supernatants is likely to be StmPr1, a 47-kDa serine protease whose gene sequence encodes a signal sequence (23).…”
Section: Discussionsupporting
confidence: 72%
“…Initially, casein hydrolysis was determined by spotting a 5-l aliquot of a bacterial suspension on Mueller-Hinton agar (Becton, Dickinson) containing 3% (wt/vol) skim milk (Nestle Carnation, Solon, OH) while gelatinase activity was tested by spotting bacteria on LB agar containing 4% (wt/vol) gelatin (20). Prior to being spotted on the indicator plates, bacteria were grown overnight on LB agar, resuspended in phosphate-buffered saline (PBS; Corning) to an OD 600 equal to 0.1, and diluted 1:10 in PBS.…”
Section: Methodsmentioning
confidence: 99%
“…The K279a genome sequence reveals a number of potential virulence factors and immune modulators, based upon the in vivo importance of their homologues in other bacteria (Crossman et al, 2008). These factors include type I, II, IV and V protein secretion systems, tissue-degradative exoenzymes, various pili, putative adhesins, flagella, LPS, putative exopolysaccharide, siderophores and quorum sensing (Crossman et al, 2008;Denton & Kerr, 1998;Fouhy et al, 2007;Huang & Wong, 2007;Looney et al, 2009;Minkwitz & Berg, 2001;Rocco et al, 2009;Travassos et al, 2004;Waters et al, 2007;Zgair & Chhibber, 2010b). Thus, the A/J mouse model can be used to compare wildtype K279a with its mutant derivatives in order to formally define the virulence factors of S. maltophilia.…”
Section: Resultsmentioning
confidence: 99%